1 BALL Delicacy Corner - Denis Eswar, Vijay Govindan; Patar, Asysyuura Adytia; David Henry, Deborah; Salimun, Muhammad Sufri; Abu Bakar, Jumardi (2009)
In this new globalization era, mostly people like to eat fast food. Therefore to fulfill their needs and style of living, we as the young entrepreneurs come out with one brilliant and fascinating idea that we would like to introduce in our business plan that is called 1 BALL Delicacy Corner. 1 BALL Delicacy Corner is consist of many types of balls includes seafood in the shape of balls like fish ball, crab ball, prawn ball and octopus ball. Besides that, we would like to do some variation that is chicken ball using our own great recipe. This type of business is a limited company which consists of five partners and together we are eager for the success in this new upcoming phenomenon of our business plan. From the point of view, it shows that the food industries are increasingly getting famous around all types of ages of people in this world. Besides that, the markets of food balls have less competition yet very few exist nowadays, so this is a better chance for us to take this opportunity to expand this type of fast food industry in our country. 1 Borneo Hypermall is the best and suitable place to start this 1 BALL Delicacy Corner because the location is very strategic and yet it is the most popular hypermall in Sabah and lot of people passing by at 1 Borneo Hypermall every day besides of shopping in it. This business will be commenced at the month of January 2010. A lot of preparation must be done before operating our business. We will sell this grill balls to all types of ages of people. The price is very reasonable to all customers although the economic condition is unstable nowadays. We are definitely realized that some of our competitors are well established in this business, but that is not going to be a threat to us because we will always offer high quality of grill balls by our own great secret recipe. Furthermore, there is a very good opportunity in this business due to the fact that fast foods are in high demands nowadays. We are sure that everyone has a different style of living so people would like to try new things every day. So our grill balls are the best remedy to the daily lives of all people. We will be serving professionally and efficiently and hoping that the customers will be increasing from time to time after enjoying our 1 BALL great recipes which will brings totally new excitement to all people.